DAMPAK PENATAAN PERMUKIMAN KUMUH TERHADAP PENINGKATAN KUALITAS HIDUP MASYARAKAT DI KAWASAN BAGAN DELI BELAWAN (THE IMPACTS OF SLUM STRUCTURING ON THE INCREASE IN PEOPLE’S QUALITY OF LIFE AT BAGAN DELI, BELAWAN) - Hadasa Manurung (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
Handling of slums is needed require handling so as not to reduce the value of the beauty of the city, decreasing the quality of life of the people, while reducing the level of security and comfort of the city. Fishermen's habitation has a community of residents who have an orientation to the sea, with the main livelihood as fishermen, so it is very dependent on natural conditions. RPKPP carries out slum handling with a structural approach, namely development of promanade / steigher, construction of environmental roads and the creation of clean water sources (boreholes) in the habitation. This study aims to evaluate the impact of slum habitation arrangement on improving the quality of life of people in Bagan Deli Belawan area. Quality of life is influenced by the quality of the neighborhood that can be seen through several things such as: infrastructure networks (roads, sanitation, access to clean water, etc.), health quality conditions (frequency of disease and access to health centers), improvement of the community economy (new levels of income and employment), perceptions of the physical security of the environment (disaster risk, safety and comfort). The research method uses the evaluation method, which compares the environmental conditions and conditions of the community before and after the RPKPP program. The results of this study indicate that the impact of slum settlement arrangement on improving the quality of life of people in the Bagan Deli Belawan area is still limited to increased accessibility, while for other aspects it has not had an impact. Therefore there is still a need to develop and implement the RPKPP program in the Bagan Deli area, not only in the infrastructure sector but also in terms of economic empowerment and changes in community behaviour. Keywords: slum, development plan, Bagan Deli Belawan